Analysis of Annual Plan 1995-96 Education Sector - Planning Commission (Planning Commission, 1995)
This document synthesizes the Planning Commission of India’s analysis of education sector funding and performance during the Annual Plans of 1994–95 and 1995–96, with historical context from 1983–1994. It highlights substantial increases in public investment, particularly in elementary and adult education, alongside state-wise variations in allocation and achievement. While notable progress was observed in enrollment expansion and adult literacy initiatives, gaps between targets and actual outcomes persisted due to reporting inconsistencies and implementation challenges. The analysis underscores the need for improved monitoring, data accuracy, and targeted interventions to enhance educational access, equity, and effectiveness across India.
Education Division, Planning Commission, Government Of India
Education Division, Planning Commission, Government Of India, Yojana Bhawan, New Delhi
Keywords: Education Sector Planning; Annual Plan 1995–96; Elementary Education; Adult Education; Financial Outlay; Enrollment Targets; State-Wise Allocations; Educational Expenditure Trends; Planning Commission of India; Literacy and Enrollment